Characterization of Arbuscular Mychorrizal Fungus from Sugar Palm (Arenga pinnata (Wurmb) Merr.)West Java and Banten KARAKTERISASI FUNGI MIKORIZA ARBUSKULA PADA RHIZOSFER AREN (Arenga pinnata (Wrmb) Merr.) DARI JAWA BARAT DAN BANTEN - Moh Ega Elman Miska; Ahmad Junaedi; Ade Wachjar; Irdika Mansur (Jurnal Silvikultur Tropika, 2016)
The diversity of AMF has been recorded as much as 250 types which associated with certain plants and inhabit the areas of tropical, temperate, and even the arctic. This research aims to find out the diversity of Arbuscular Mycorrhizal Fungus under the sugar palm tree stands in different locations. Soil were sampled from the rhizosphere of sugar palm in three subdistricts i.e. Cianjur, Sukabumi, and Lebak. These samples were processed directly by wet sieving and sentrifugation method to separate the AMF spore., These spores were then identified immediately. The results showed there were four genera and 14 morpho types AMF spores, which consists of: seven types of Glomus sp.; five types of Acaulospora sp.; one Scutellospora sp.; and one Gigaspora sp.Key words : AMF, Banten, diversity, sugar palm, West Java.